2011
DOI: 10.1007/s10555-011-9271-6
|View full text |Cite
|
Sign up to set email alerts
|

External validation of a model to predict the survival of patients presenting with a spinal epidural metastasis

Abstract: The surgical treatment of spinal metastases is evolving. The major problem is the selection of patients who may benefit from surgical treatment. One of the criteria is an expected survival of at least 3 months. A prediction model has been previously developed. The present study has been performed in order to validate externally the model and to demonstrate that this model can be generalized to other institutions and other countries than the Netherlands. Data of 356 patients from five centers in Germany, Spain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In this study, death occurred in 92% of cases, 9 months (95% CI [3][4][5][6][7][8][9][10][11][12][13][14] after the diagnosis of compression syndrome. A similar result was found in others studies, who reports that the overall survival of patients with compression syndrome was 9 months 15 and 12 months 16 after the development of neurological signs. Significantly, longer survival is associated with a longer interval between diagnosis of the tumor and the development of compression syndrome 12 .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, death occurred in 92% of cases, 9 months (95% CI [3][4][5][6][7][8][9][10][11][12][13][14] after the diagnosis of compression syndrome. A similar result was found in others studies, who reports that the overall survival of patients with compression syndrome was 9 months 15 and 12 months 16 after the development of neurological signs. Significantly, longer survival is associated with a longer interval between diagnosis of the tumor and the development of compression syndrome 12 .…”
Section: Discussionsupporting
confidence: 91%
“…The larger importance of visceral metastases compared to bony metastases in predicting survival in this study concurs with other studies. [4][5][6]28 Clearly from the above, the similar overall ability of the scoring systems to predict survival hides major differences in performance between individual items within each system. It is therefore not surprising that prediction of survival improved after combining the most predictive items (Nagelkerke's R 2 = 0.31 vs Nagelkerke's R 2 = 0.15 to 0.18 for the original systems).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, many other studies have found the same positive correlation between general condition and survival as our study. 6,10,12,27,28 Tomita et al 2 believed that the general condition was reflective of the status of the visceral metastasis, although they did not investigate this proposed link.…”
Section: Discussionmentioning
confidence: 99%
“…These models have been developed and partially validated in Dutch patients and are therefore considered to be valid for use with Dutch patient populations. The Van der Linden model has already been successfully validated in the Canadian population [49] and the Bartels model has also been geographically and prospectively validated [48,61]; nevertheless, these models should be validated further for truly international use. These models were based on current clinical practice; however, new treatment options are currently being developed, and are expected to increase the survival of patients with spinal metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Details of these prognostic models can be found in Table 4. The accuracy of the Tokuhashi model is reported to vary greatly [43][44][45][46][47], but the other models have been shown to permit a reliable assessment of the survival of patients with symptomatic spinal metastases, with no model being superior to the others [11,48,49].…”
Section: Assessing Survivalmentioning
confidence: 99%